Investigating the impact of polymorphisms in the ANKK1 and DRD2 genes on oral health-related quality of life in male patients with temporomandibular disorders - Baratto, Samantha Schaffer Pugsley; Abuabara, Allan; Bueno, Débora Cristina Cardozo; Matos, Thalita de Paris; Perin, Camila Paiva; Correr, Gisele Maria; Lepri, César Penazzo; Kirschneck, Christian; Baratto-Filho, Flares; Küchler, Erika Calvano (Frontiers in Oral Health, 2025)
IntroductionPrevious studies have reported that genetic polymorphisms may impact the signs and symptoms of temporomandibular disorder (TMD). Therefore, this study aimed to investigate the association between polymorphisms in the Dopamine Receptor D2 (DRD2) and Ankyrin Repeat and Kinase Domain Containing 1 (ANKK1) genes and oral health-related quality of life of male patients with TMD.MethodsThis cross-sectional study included construction workers with at least one sign or symptom of TMD. The reduced version of the Oral Health Impact Profile questionnaire (OHIP-14) was used to assess oral health-related quality of life. Genomic DNA was used to genotype genetic polymorphisms in the locus 11q22-q23, one in ANKK1 (rs1800497) and two in DRD2 (rs6275 and rs6276), using real-time polymerase chain reaction. The total OHIP-14 score and those for each domain were compared among the genotypes using the Kruskal–Wallis test and Dunn's test in the genotypic co-dominant model. The Mann–Whitney test was used in the recessive model (alpha = 0.05).ResultsThe sample included a total of 114 male patients. OHIP-14 total score ranged from 0 to 33. Chronic pain (87.7%), followed by disc displacement (38.2%), was the most common sign and symptom observed. All the genetic polymorphisms assessed were within the Hardy–Weinberg equilibrium. The “Handicap” domain (D6) was statistically associated with the genetic polymorphism rs1800497 in ANKK1 (p = 0.008). The genetic polymorphism rs1800497 Taq1A in DRD2/ANKK1 was associated with oral health-related quality of life, as measured by the handicap domain in OHIP-14, in male patients with TMD.DiscussionThis study showed that genetic polymorphisms can negatively impact the oral health-related quality of life, as measured by the handicap domain of the OHIP-14. The physical and emotional condition of patients, together with biological pathways, should receive more attention in future studies, and personalized treatment plans should be created to improve patients' quality of life.